China`s xinjiang policy: an analysis based on the theory of relative deprivation - Nur Shahadah Jamil (Penerbit UKM, 2011)
Xinjiang, which is China’s western province that comprised 18 percent of the country’s total land area and heavily populated by non-Han Chinese ethnic minorities, is a region increasingly beset by the problem of confrontation between two very distinct groups- the more recently arrived Han and the indigenous Uighur Turkish Muslims. The confrontation revolves primarily around the struggle for domination over the province between the two, and also Uighur quest for greater autonomy rights or even independence from the government of the Chinese Communist Party (CCP). In order to tackle these problems, the government of CCP has already taken and implemented both coercive and persuasive measures and policies in Xinjiang since the establishment of the People’s Republic of China in 1949. However, disturbances by ethnic minorities in Xinjiang such as violent demonstrations and ethnic clashes continue and can recur anytime in the future with little forewarning if necessary steps were not taken. All these, reflect the failure of CCP government’s policies towards Xinjiang in its efforts to ensure stability in the region. To what extend the effectiveness of CCP’s policies towards Xinjiang depends on the factor of relative deprivation (RD) that exist among the minorities in Xinjiang, particularly the Uighurs when they compare themselves with their Han counterparts that obviously have better living conditions compared to them.